Structure of thrombin, a Janus-headed proteinase - Bode, Wolfram (Henry Stewart Talks, 2007)
Coagulation, Prothrombin activation, Thrombin structure and surface, Anion binding exosite I, Specific thrombin inhibitors from haematophagous animals, Interaction with the PARs, Fibrinogen, Staphylocoagulase, Direct thrombin inhibitors, Heparin binding, Thrombomodulin binding and function
Reviewed at 2015/08/31